The Implementation of Occupational Health and Safety Management System (OHS Management System) to Improve Human Resource Development Performance - Widhiastuti, Hardani; Asih, Gusti Yuli; Kurniawan, Yudi (Universitas Muhammadiyah Surakarta, 2019)
This research emphasizes Human Resource Development Performanceexistence which is not as expected, one of the causes is the OHS Management System. Our research aims to explain the performance of human resource development by looking at the impact of Occupational Health and Safety systems, work stress caused and how motivational the role of management is. This research was conducted to produce a Model and the results of the analysis of the Occupational Health and Safety System (OHS MANAGEMENT SYSTEM ) associated with HR Development Performance, with 80 research subjects as employees of PT.PLN Pesero APD Central Java and DIY. This research used quantitative research methods that use Descriptive Statistics and analysis of the effect of each variable using the Partial Least Square (PLS) technique. Based on the results of the calculation of Q square obtained Q square value of 0.60. This showed that the Q square value was greater than 0.5 which means it could be said that the factor of OHS management system, Work Stress and OHS Management Motivation has a good prediction level on the Performance of Human Resources Management. The disadvantage of this study is that because the employees are employees of PT PLN Pesero APD Central Java and DIY, the location of the study always changes depending on the working area. In addition, working conditions and situations greatly affect when subjects fill out questionnaires, bearing in mind that their assignments are very heavy because they are related to the regulation of the electricity load for the Network throughout Indonesia.